Partial defoliation improves must quality of cv. Albariño infected by Grapevine leafroll associated virus 3 - PEREIRA-CRESPO, Sonia; SEGURA, Antonio; GARCÍA-BERRIOS, Julián; CABALEIRO, Cristina (Phytopathologia Mediterranea, 2012)
The effect of leaf removal treatments around vine cluster zones on must quality were tested during 2003 and 2004 in Rías Baixas (Spain) in two Albariño vineyards infected by GLRaV-3. As expected, the main virus damage was decreased sugar content (2.1 Brix in 2003 and 0.9 Brix in 2004) in the musts compared with leafroll-free plants. Leaf removal improved must quality by decreasing titratable acidity by between 0.5 and 1.9 g L-1 of tartaric acid, depending on the experiment; it also increased the grape sugar content an average of 1 Brix. In vineyards with high incidence of GLRaV-3, partial defoliation at veraison, or 2 to 3 weeks later, had an improved must quality, counteracting the negative impact of the virus. This process is recommended to avoid penalties in wineries during years with poor ripening conditions.